Pelestarian Wayang Golek di Padepokan Giri Harja Jelekong Kabupaten Bandung Jawa Barat 2009-2018 - Nitri Anhari Muflihatul Salma; Tarpin Tarpin (UIN Sunan Gunung Djati Bandung, 2019)
This study discusses Padepokan Giri Harja in wayang golek in West Java. The selection of Padepokan to be studied is very important because it has influence and role in the preservation of puppet shows in Jelekong village, West Java. The purpose of this study is the first to: find out the history and development of Padepokan Giri Harja, know Gait Asep Sunadar Sunarya in the development of Padepokan Giri Harja, and know Padepokan Giri Harja in preserving Wayang Golek The method used in this study is the historical method, which is a method that reconstructs history by studying events in the past. There are four stages in this method, the first stage of Heuristics is the search for sources, the second stage of criticism namely internal criticism and external criticism, the third stage of interpretation, i and the fourth stage of historiography. The results of this study indicate that the founder of Padepokan Pusaka Giri Harja was Abah Sunarya. This Padepokan is a place for puppet puppet puppetry course. This Padepokan is located in Jelekong village, Ciparay Subdistrict, Bandung Regency, West Java. Many of his students later became successful puppeteers, including his own children. Abeng Sunarya was once a member of the management of the Bandung Regency Pedalangan and Pepadi Foundation. After Abah Sunarya died, the heritage of Giri Harja was continued by her son, Asep Sunandar Sunarya, better known as Giri Harja 3 or Abah Asep. Abah Asep developed this Heritage of Giri Harja so well that he had the desire to build a hermitage to make it easier for people who wanted to practice puppet show. The presence of Padepokan Seni Padalangan Giri Harja is one of the icons of the art village. The permanent building with the shape of a typical gunungan roof of wayang golek stands majestically on Jalan Raya Laswi, across the Bandung-Majalaya region, West Java, which is equipped with a large parking lot. The famous puppeteer Asep Sunandar Sunarya (deceased) planned the building to become the Padepokan Seni Boarding School Padalangan that scored reliable puppeteers as well as a form of preservation and inheritance of puppet show art to the younger generation.